Lactobacillus reuteri ZJ617 maintains intestinal integrity via regulating tight junction, autophagy and apoptosis in mice challenged with lipopolysaccharide - Cui, Yanjun (Oncotarget, 2017)
Live probiotics are effective in reducing gut permeability and inflammation. We have previously reported that Lactobacillus reuteri ZJ617 (ZJ617) with high adhesive and Lactobacillus rhamnosus GG (LGG) can ameliorate intestine inflammation induced by lipopolysaccharide (LPS). The present study was aimed at elucidating the roles of ZJ617 and LGG in alleviating the LPS-induced barrier dysfunction of ileum in mice. Six C57BL/6 mice per group were orally inoculated with ZJ617 or LGG for one week (1× 10(8) CFU/mouse) and intraperitoneally injected with LPS (10 mg/kg body weight) for 24 h. The results demonstrated that pretreatment with ZJ617 and LGG attenuated LPS-induced increase in intestinal permeability. The probiotics supplementation suppressed LPS-induced oxidative stress. Both ZJ617 and LGG strongly reversed the decline of occludin and claudin-3 expression induced by LPS challenge. ZJ617 relieved LPS-induced apoptosis by decreasing caspase-3 activity. Noticeably, ratio of microtubule-associated light chain 3 (LC3)-II/LC3-I and LC3 activity were elevated by LPS stimulation, whereas such increases were obviously attenuated by both of the probiotics treatment. Moreover, phosphorylated mammalian target of rapamycin (p-mTOR) was significantly inhibited by LPS, whereas complementation of ZJ617 and LGG markedly increased the expression of p-mTOR. Collectively, our results indicated that ZJ617 could protect LPS-induced intestinal barrier dysfunction via enhancing antioxidant activities and tight junction and attenuating apoptosis and autophagy via mTOR signaling pathway. These findings could serve as systematic mechanisms through which probiotics promote and maintain gut homeostasis.